Understanding Immune Cells in Tertiary Lymphoid Organ Development: It Is All Starting to Come Together - Jones, Gareth W.; Hill, David G.; Jones, Simon A. (Frontiers in Immunology, 2016)
Tertiary lymphoid organs (TLOs) are frequently observed in tissues affected by non-resolving inflammation as a result of infection, autoimmunity, cancer and allograft rejection. These highly ordered structures resemble the cellular composition of lymphoid follicles typically associated with the spleen and lymph node compartments. Although TLOs within tissues show varying degrees of organisation, they frequently display evidence of segregated T and B cell zones, follicular dendritic cell networks, a supporting stromal reticulum and high endothelial venules. In this respect, they mimic the activities of germinal centres and contribute to the local control of adaptive immune responses. Studies in various disease settings have described how these structures contribute to either beneficial or deleterious outcomes. While the development and architectural organisation of TLOs within inflamed tissues requires homeostatic chemokines, lymphoid and inflammatory cytokines and adhesion molecules, our understanding of the cells responsible for triggering these events is still evolving. Over the past 10-15 years novel immune cell subsets have been discovered that have more recently been implicated in the control of TLO development and function. In this review we will discuss the contribution of these cell types and consider the potential to develop new therapeutic strategies that target TLOs.